The changing face of clay : continuity and change in the transition from village to urban life in the Near East - Wengrow, David
In the Near East, the inherent dualism of clay as both symbol and instrument was a feature of its use from the inception of farming villages to the formation of cities, and the extensive record of its 'changing face' allows us to trace the continuous history of development between them.